2021
DOI: 10.1002/fsn3.2608
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of risk factors and correlation in large sample from the perspective of hypoglycemia

Abstract: Hypoglycemia is defined several types, including severe hypoglycemia, symptomatic, and asymptomatic hypoglycemia (all blood glucose ≤70 mg/dl, but the symptoms are different), which may be hypoglycemia (symptomatic, but blood glucose is unknown) and relative hypoglycemia (symptomatic but still more than 70 mg/ dl) (Smith et al., 2018). The incidence of hypoglycemia has not been significantly lower in diabetic patients with improved blood glucose management and increased use of insulin (Holt, 2019).Studies sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Although large abdominal circumference is harmful to physical health, a small abdominal circumference can increase the risk of hypoglycemia. A large-sample study on risk factors for hypoglycemia in patients with T2DM showed that, for every 3cm increases in abdominal circumference, the risk of hypoglycemia decreases by 7.1% [31] . An RCT showed that for every 1 cm decrease in abdominal circumference, the risk of severe hypoglycemia in older adults with T2DM increased 7% [32] .…”
Section: Discussionmentioning
confidence: 99%
“…Although large abdominal circumference is harmful to physical health, a small abdominal circumference can increase the risk of hypoglycemia. A large-sample study on risk factors for hypoglycemia in patients with T2DM showed that, for every 3cm increases in abdominal circumference, the risk of hypoglycemia decreases by 7.1% [31] . An RCT showed that for every 1 cm decrease in abdominal circumference, the risk of severe hypoglycemia in older adults with T2DM increased 7% [32] .…”
Section: Discussionmentioning
confidence: 99%